Interculturality Of Indonesia Sundanese Religion In West Java - Sukarna, Timotius; Ming, David; Windarti, Maria Titik (Jayapangus Press, 2023)
This research identified the construction of Sundanese culture in the Sundanese religion of West Java.The discussion of this paper describes the existence of the Sundanese religion in the Sundanese Tatar, Sundanese also Christianity in the Sundanese Tatar. The population total in Tatar Sunda or West Java which amounted to 38,668,115 people, there are 1,051,670 Christians, meaning that Christians in West Java are only 2.72% of the total population. That is why through this manuscript research how religious tolerance in diversity can be realized which is a philosophy that is expected to be realized in religious life in the Republic of Indonesia based on Pancasila. All religions in Indonesia, both those that adhere to the majority and minorities, have agreed to uphold the core values ​​contained in Pancasila.